1990
DOI: 10.2307/1966716
|View full text |Cite
|
Sign up to set email alerts
|

User's Perspective of Counseling Training in Ghana: The "Mystery Client" Trial

Abstract: Evaluating counseling training programs from the client's perspective has posed a methodological challenge for family planning researchers. This report describes an evaluation method that combines clinic observation with an exit interview methodology. Eighteen women posing as clients were requested to visit three clinics with trained and three clinics with untrained family planning counselors. These clients (called "mystery clients" in Ghana) were later interviewed to uncover any perceived differences between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 5 publications
1
23
0
Order By: Relevance
“…This included information from verbal communication during sessions with health care providers and/or information in printed format, such as posters or pamphlets. Fourteen of the reviewed evaluations/studies (46.6%) indicated that MCs found the information provided by the health care providers to be insufficient [2,5,6,13,17,20,23,26–31,33,36,37] The following quotes, from studies in Uganda, Mexico, and Nicaragua, indicate examples of lack of quality information provided; “…none of the organizations visited had tailor-made targeted information, education and communication (IEC) materials for YMSM and LGBTQ youth” (Uganda) [36]. …”
Section: Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…This included information from verbal communication during sessions with health care providers and/or information in printed format, such as posters or pamphlets. Fourteen of the reviewed evaluations/studies (46.6%) indicated that MCs found the information provided by the health care providers to be insufficient [2,5,6,13,17,20,23,26–31,33,36,37] The following quotes, from studies in Uganda, Mexico, and Nicaragua, indicate examples of lack of quality information provided; “…none of the organizations visited had tailor-made targeted information, education and communication (IEC) materials for YMSM and LGBTQ youth” (Uganda) [36]. …”
Section: Key Findingsmentioning
confidence: 99%
“…MC methodology has been used in health research for more than 20 years [2,3], and Gonsalves and Hindin’s recent review on youth access to SRH care in pharmacies includes studies that involved mystery clients [4]. However, there are no systematic reviews published to our knowledge that analyse the uses, advantages, and disadvantages of MC methodology in adolescent sexual and reproductive health (ASRH) research and monitoring and evaluation (M&E) of programmes.…”
Section: Introductionmentioning
confidence: 99%
“…According to several studies, adolescents often feel unwelcome, perceive providers as being rude, or are refused services. [16][17][18] Adolescents report other barriers to seeking care at public health facilities, including cost, the fear that services are not going to be confidential and the fear of meeting their parents or other adults they know at the health care facility. 7,19 To understand how best to promote STI treatment among Nigerian youth, it is critical that we understand their treatment-seeking behaviors.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Mystery client methodology, previously used in SA, [34] is employed as a strategy to evade biases that occur during direct observations of service delivery. [26,35] While mystery clients can mimic some aspects of 'real' callers, however, there are clearly limitations in doing so. The demographics, tone of voice and emotions expressed by mystery clients are likely to differ from those of a 'real' caller trying to come to terms with a recent diagnosis of HIV, for example.…”
Section: Discussionmentioning
confidence: 99%